Male physique. (London : Man & Art Publishing Ltd., 1960)
Fonds Suzan Daniel (FSD)
Ondertitel vanaf (1963) 17 : 'The international Lon magazine'
Periodiciteit : driemaandelijks
Redactie : Suite 4, 119 Oxford Street, London W.1 ; vanaf (1962) 14 : 85,Lillie oad, London S.W.6 ; vanaf (1963) 17 : Lon de New York, 112 Rue St. Maur, Paris
Engels
Periodiek